The virtual annual general meeting in Germany: A theoretical and empirical analysis of design possibilities and future prospects - Patrick Ulrich; Ramona Zettl (New outlooks for the scholarly research in corporate governance, 2023)
JOURNAL MENU THE VIRTUAL ANNUAL GENERAL MEETING IN GERMANY: A THEORETICAL AND EMPIRICAL ANALYSIS OF DESIGN POSSIBILITIES AND FUTURE PROSPECTS DOWNLOAD THIS ARTICLE Patrick Ulrich ORCID logo, Ramona Zettl https://doi.org/10.22495/nosrcgp22 Creative Commons License This work is licensed under a Creative Commons Attribution 4.0 International License. Abstact The following study shows theoretical and empirical evidence regarding the use of virtual annual general meetings in Germany. This has become commonplace during COVID-19. At the moment, there is an ongoing discussion on the chances and disadvantages of virtual annual shareholders’ meeting (AGM) in Germany